Phacomatosis Pigmentovascularis and Extensive Venous Malformation of Brain Vessels: An Unknown Association or a New Vascular Neurocutaneous Syndrome? - Toelle, S. P.; Weibel, L.; Schiegl, H.; Boltshauser, E. (Neuropediatrics, 2011)
We report on a 16-year-old intelligent and sportive boy with the cutaneous findings of phacomatosis pigmentovascularis unclassifiable type.The skin anomaly was lateralised to his left body side since birth, fading over the years. Because of headache and dizziness, brain magnetic resonance imaging was performed, which revealed an impressive enlargement of subependymal, deep and superficial medullary veins on the right side combined with a mild atrophy of the ipsilateral parietal region. We propose to investigate patients with phacomatosis pigmentovascularis for associated venous brain malformations with adequate imaging techniques.
Keywords: phacomatosis pigmentovascularis; twin spotting; venous malformations